2013
DOI: 10.1002/bit.24856
|View full text |Cite
|
Sign up to set email alerts
|

Influence of outer membrane c‐type cytochromes on particle size and activity of extracellular nanoparticles produced by Shewanella oneidensis

Abstract: The metal-reducing bacterium Shewanella oneidensis is capable of reducing various metal(loid)s and produces nanoparticles (NPs) extracellularly, in which outer membrane c-type cytochromes (OMCs) have been suggested to play important roles. The objective of this study was to investigate the influence of the OMCs, that is, MtrC and OmcA, on the size and activity of the extracellular silver NPs (AgNPs) and silver sulfide NPs (Ag(2)S NPs) produced by S. oneidensis MR-1. We found that (i) the lack of OMCs on S. one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 46 publications
0
61
1
Order By: Relevance
“…A 1.6-ml outlet sample was filtered through a 0.22-m syringe filter and mixed with 0.2 ml of 0.5 g/liter s-diphenylcarbazide in 10% methanol-12.5 mM H 2 SO 4 followed by OD 540 measurement after a 20-min incubation. At the end of the Cr(VI) immobilization experiment, a portion of the biofilms in the reactors was analyzed using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) (34). The samples were dried and sputtered with Pt.…”
Section: Methodsmentioning
confidence: 99%
“…A 1.6-ml outlet sample was filtered through a 0.22-m syringe filter and mixed with 0.2 ml of 0.5 g/liter s-diphenylcarbazide in 10% methanol-12.5 mM H 2 SO 4 followed by OD 540 measurement after a 20-min incubation. At the end of the Cr(VI) immobilization experiment, a portion of the biofilms in the reactors was analyzed using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) (34). The samples were dried and sputtered with Pt.…”
Section: Methodsmentioning
confidence: 99%
“…There have been reports on the biosynthesis of metal nanoparticles using Shewanella species (Ng et al 2013;Suresh et al 2011), but the physical factors for optimization have rarely been reported. Therefore, it is critical and meaningful to explore the optimal conditions of Au@NP biofabrication by SXM and MR-1.…”
Section: Effect Of Phmentioning
confidence: 99%
“…In the MR-1 strain, the outer membrane c-type cytochromes, MtrC and OmcA, were considered as important proteins for metal reduction (Wu et al 2013a). However, the MR-1 wild type and its mutants omcA and mtrC were still capable of reducing Au 3+ into Au@NPs (Wu et al 2013b), while the particle size of the extracellular nanoparticles were decreased mtrC and omcA mutants (Ng et al 2013). On the other hand, Shewanella xiamenensis, which is isolated from coastal sediment collected off Xiamen, China, is a close-related strain to S. oneidensis based on phylogenetic tree analysis by 16S rRNA and gyrase gene (Huang et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Primarily, a final redox reaction that proceeds through MtrC and OmcA have important roles in the reduction of various metal ions, including Pd(IV), U(VI), Ag(I), and Fe(III). 1,[13][14][15] Previous studies showed that the reduction of Au(III) ion to gold nanoparticles (Au NPs) was successfully performed using S. oneidensis, and that Au NPs were produced on the bacterial surface. 2,16 However, the contribution of the bacterial surface structure to the production of Au NPs remained unclear.…”
mentioning
confidence: 99%